Business ethics and corporate social responsibility - Griseri, Paul; Seppala, Nina (Australia : South-Western, Cengage Learning, 2010)
A new text for new realities: "Business Ethics & Corporate Social Responsibility" charts a course for students through the unprecedented challenges and turbulence of modern business and its implications for people across the globe. Moving beyond the Anglo-American focus of existing works, the authors employ a refreshingly international perspective to leave students with a broad and reflective understanding of business ethics. A flexible 3-part structure, developed from extensive market feedback, aligns with the latest course structures, while a strong focus on environmental ethics and sustainability throughout provides market-leading coverage of this vital issue. An unparalleled range of case studies, including chapter cases and longer premium cases supplied by HBR, Ivey and ECCH, combine with a full set of online supporting resources to make this the complete introduction to business ethics in a rapidly evolving world
1. Understanding corporate social responsibility -- 2. Stakeholder management -- 3. Theories of ethics -- 4. Environmental ethics -- 5. The behavioural context -- 6. Ethics and corporate social responsibility in a global context -- 7. the business of human rights -- 8. Civil society organizations -- 9. Governing organizations -- 10. Auditing and reporting social performance -- 11. Managing ethics internally -- 12. Responsibility in managing people and operations -- 13. Environmental responsibility -- 14. Giving back to society
Includes bibliographical references and index
Keywords: Business ethics; Social responsibility of business